Evaluation of the synergistic effects of epigallocatechin-3-gallate-loaded PEGylated-PLGA nanoparticles with nimodipine against neuronal injury after subarachnoid hemorrhage - Yang, Xianguang; Han, Mengguo; Wang, Xue; Wang, Jian; Sun, Xiaoxue; Zhang, Chunyan; Yan, Shuaiguo; Huang, Liyong; Chen, Ying (Frontiers in Nutrition, 2023)
Subarachnoid hemorrhage (SAH) is a devastating subtype of stroke with high mortality and morbidity. Although serious side effects might occur, nimodipine, a second-generation 1,4-dihydropyridine calcium channel blocker, is clinically used to improve neurological outcomes after SAH. Recently, (-)-epigallocatechin-3-gallate (EGCG) has been reported to inhibit Ca2+ overloading-induced mitochondrial dysfunction, oxidative stress, and neuronal cell death after SAH; however, low bioavailability, instability, and cytotoxicity at a high dose limited the clinical application of EGCG. To overcome these limitations, PEGylated-PLGA EGCG nanoparticles (EGCG-NPs) were constructed to enhance the bioavailability by using the double-emulsion method. Antioxidative activity, cytotoxicity, behavioral, and immunohistochemistry studies were carried out to determine the neuroprotective effectiveness after cotreatment with EGCG-NPs (75 mg/kg/d preconditioning for 7 days before SAH) and nimodipine (10 mg/kg/d after 30 min of SAH) by using in vivo SAH models. The optimized EGCG-NPs with a Box–Behnken design showed a small particle size of 167 nm, a zeta potential value of −22.6 mV, an encapsulation efficiency of 86%, and a sustained-release profile up to 8 days in vitro. Furthermore, EGCG-NPs (75 mg/kg/d) had superior antioxidative activity to free EGCG (100 mg/kg/d). EGCG-NPs combined with nimodipine exhibited significant synergistic effects against neuronal cell death by suppressing oxidative stress, Ca2+ overloading, mitochondrial dysfunction, and autophagy after SAH. These results suggest that cotreatment with EGCG-NPs and nimodipine may serve as a promising novel strategy for the treatment of SAH.